(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the morphemic structure of the English language and its significance in linguistic studies. The concept of the morpheme, its main types, and its role in word formation and grammatical structure are analyzed. Special attention is paid to the importance of morphemic analysis in understanding the internal structure of English words. The article also highlights how learning morphemes can help language learners expand their vocabulary and develop overall language competence.